Sistem Suggestion dengan Metode TOPSIS untuk Meningkatkan Keberhasilan Serious Game Greenlife Town - Edward Manhattan Prasetio; Gregorius Satia Budhi; Hans Juwiantho (Jurnal Infra, 2022)
Indonesia has a huge potential for renewable energy sources. However, this potential has not been fully utilized. One of the reasons is that the Indonesian people still do not understand renewable energy sources properly. Due to a lack of understanding and education, very few people are motivated to advance renewable energy sources in Indonesia. The solution to this problem is to create a platform for education to encourage. The platform is in the form of Serious Game. However, in practice, players often find it difficult to complete the game, so that the player's focus is more on solving problems than receiving information. Therefore, this thesis also utilizes the suggestion system to provide assistance options to players using the TOPSIS method. The test results show that the suggestion system is not able to increase the success of players in completing the game. The resulting effect is the opposite, where players increasingly have a worse final score even touching the number 88%. This failure is not solely caused by the method used, but also the way the method is implemented, the user convenience in playing, and the form of testing that is less flexible.